Safety and efficacy of azacitidine in myelodysplastic syndromes - Carlos E Vigil; Taida Martin-Santos; Guillermo Garcia-Manero (Dove Medical Press, 2010)
Carlos E Vigil, Taida Martin-Santos, Guillermo Garcia-ManeroDepartment of Leukemia, The University of Texas MD Anderson Cancer Center, Houston, TX, USAPurpose: The clinical efficacy, different dosages, treatment schedules, and safety of azacitidine are reviewed.Summary: Azacitidine is the first drug FDA-approved for the treatment of myelodysplastic syndromes that has demonstrated improvements in overall survival and delaying time to progression to acute myelogenous leukemia. The recommended dosage of azacitidine is 75 mg/m2 daily for 7 days, with different treatment schedules validated. It appears to be well tolerated, with the most common adverse effects being myelosuppression. Several other off-label recommendations were also analyzed.Conclusion: Azacitidine is the first DNA hypomethylating agent approved by FDA for the treatment of myelodysplastic syndromes with demonstrated efficacy.Keywords: Azacitidine, MDS, hypomethylating agents